Systematic evaluation on the physicochemical characteristics of a series polysaccharides extracted from different edible lilies by ultrasound and subcritical water - Song, Zihan; Zhang, Yanli; Luo, Yulin; Ti, Yongrui; Wang, Weizhen; Ban, Yuqian; Tang, Yuchao; Hou, Yuqing; Xu, Leifeng; Ming, Jun; Yang, Panpan (Frontiers in Nutrition, 2022)
A series polysaccharide samples extracted from three edible lilies (Lilium davidii var. willmottiae, Lilium brownii var. viridulum and Lilium lancifolium) by subcritical water and ultrasound-assisted extraction were systematically compared. The results showed that extraction method was a more important factor than lily species. Subcritical water extracted lily polysaccharides (S-LP) with higher yield, molecular weight, neutral glucose and uronic acid content as well as apparent viscosity. Ultrasound-assisted extracted lily polysaccharides (U-LP) with higher reducing sugars and protein content. Moreover, due to the degradation of glycosidic bonds, ultrasonic extraction was easier to obtain lower molecular weight polysaccharides. In addition, the extraction method significantly affected the monosaccharide proportion of polysaccharides, but had no effect on type. Glucose was the main component in S-LP, and glucose and mannose were the main components in U-LP. The micromorphology of different polysaccharide samples was similar, and the SEM images showed regular/irregular particle clusters with different particle sizes. Overall, the relationships between extraction methods, lily species and polysaccharide properties were preliminarily elucidated, providing a reference for the targeted extraction of specific lily polysaccharides.